Images ottomanes dans la littérature croate : Marulic (1450-1524), Gundulic (1589-1638), Mazuranic (1814-1891) - Sineva Bene-Katunarić (Cahiers Balkaniques)
Over three centuries, some Croatian regions were in the geopolitical situation which could be qualified as between “the devil and the deep sea”, as far as they were under Venetian and Ottoman domination. In literature, the Ottoman occupation was a very fertile thematic field. Four major Croatian writers: Marko Marulić (16th century), Ivan Djivo Gundulić (17th), Ivan Mažuranić (19th) and Miroslav Krleža (20th) fictionalised the Ottoman topics. Hereby, we propose to study phenomena of transposition, i.e. shifting and sliding of historical items in the process of their aesthetic realisation. Why the literary transposition is contemporary to events by which it was inspired only in the case of Marulić and to some extent in the case of Gundulić? Why Gundulić and Mažuranić displaced the fictional topics of their epic poems Osman and The Death of Smail-Aga Čengić far from Croatian countries. Why Krleža used the form of ballads to treat this subject? What role the Christian Occident was supposed to play in four oeuvres? Did the literary transcription of fight against Ottomans contribute in the building of identity imaginary of Croatians.